2017
DOI: 10.1017/s0007123416000569
|View full text |Cite
|
Sign up to set email alerts
|

Clerics and Scriptures: Experimentally Disentangling the Influence of Religious Authority in Afghanistan

Abstract: This article unpacks the psychological influence of a Muslim cleric’s power to mobilize for collective action in an experiment in Afghanistan. The same cleric requests contributions for a hospital from day laborers when dressed as a civilian and as a cleric. InCiviliancondition, 50 per cent contributed and 17 per cent made large contributions; inClericcondition, 83 per cent contributed but average giving did not increase as most gave the smallest possible amount. Inclusion of a recitation of Qur’anic verses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…Where armed groups invoke religious doctrine to justify violence and recruit supporters, policymakers increasingly amplify the voices of moderate religious leaders as credible sources of pro-peace messaging. Many of these interventions draw on research that finds that religious leaders can encourage pro-social attitudes and behaviors by the nature of their divinely-ordained authority, by promising divine rewards, or by drawing on scripture to persuade the faithful (Masoud, Jamal and Nugent 2016;Condra, Isaqzadeh and Linardi 2019). Spreading the messages shared by these leaders is part of a broader strategy to counter violent extremism by winning the hearts and minds of potential recruits (Berman, Felter and Shapiro 2020).…”
Section: Theoretical Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Where armed groups invoke religious doctrine to justify violence and recruit supporters, policymakers increasingly amplify the voices of moderate religious leaders as credible sources of pro-peace messaging. Many of these interventions draw on research that finds that religious leaders can encourage pro-social attitudes and behaviors by the nature of their divinely-ordained authority, by promising divine rewards, or by drawing on scripture to persuade the faithful (Masoud, Jamal and Nugent 2016;Condra, Isaqzadeh and Linardi 2019). Spreading the messages shared by these leaders is part of a broader strategy to counter violent extremism by winning the hearts and minds of potential recruits (Berman, Felter and Shapiro 2020).…”
Section: Theoretical Motivationmentioning
confidence: 99%
“…Drawing upon recent studies emphasizing the importance of religious messaging, this article tests whether religious appeals for peace shift at-risk youths' attitudes and behavior toward out-groups and violent extremism in a setting with a growing Islamic extremist insurgency (McClendon and Riedl 2015;Masoud, Jamal and Nugent 2016;Condra, Isaqzadeh and Linardi 2019). International collaboration with local, moderate religious leaders has become an increasingly popular strategy to disseminate appeals for tolerance and counteract extremist narratives (Blair et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the Qur'an group was more likely to support women's political leadership compared to a control group that received the same argument without Qur'anic support. And most recently, Condra, Isaqzadeh, and Linardi (2019) reported that participants in Afghanistan who were presented with specific Qur'anic verses were significantly more likely to donate large sums of money to charity than the control group. While the treatment in both studies consisted of exposure to authoritative texts versus no exposure (rather than varying the content of the text between groups), both studies suggest that exposure to messages in authoritative religious texts yields significant attitudinal results.…”
Section: Where Do Biblical Interpretations Come From?mentioning
confidence: 99%
“…Indeed, research has shown that religious leaders have a large and substantive influence on a host of controversial moral political issues, even when these messages are crosscutting (Djupe and Calfano 2013;Ben-Nun Bloom, Arikan, and Courtemanche 2015;Masoud, Jamal, and Nugent 2016;Margolis 2018). Moreover, exposure to religious teachings leads to more charitable giving and pro-social behavior (Warner et al 2015;McClendon and Riedl 2015;Condra, Isaqzadeh, and Linardi 2017). Finally, religious leaders can also use prayer times to mobilize for street protests (Butt 2016).…”
Section: Indivisible Territory and Different Types Of Conflictmentioning
confidence: 99%